544-971 MECHANISM OF H2 O VAPOR ADSORPTION IN A TYPE ZEOLITES. THE ADSORPTION ISOTHERMS - Davlatova, odina (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In this study, the energy characteristics of water vapor adsorption in NaA and NaA(NaBO2) zeolites were measured by adsorption calorimetry. Information of differential heats, isotherms, entropy and kinetic of adsorption in the matrix of NaA and NaA(NaBO2) zeolites were obtained. Adsorption isotherms (a) and differential heats of adsorption (Qd) of water vapor by NaA and NaA(NaBO2) zeolites were measured at 303 K. The heats of adsorption are stepwise and each step corresponds to the stoichiometric formation of adsorption complexes of H2O molecules with Na+ or H+ ions, (H2O)n/Na+ or H+, (n = 1-4), which are located on the SIII, SII and SI crystallographic positions of NaA and NaA(NaBO2). Hydration mechanism of NaA and NaA(NaBO2) are complex and at saturation, the zeolites are occupied by the next water zeolitic host/guest systems: NaA – 2.2[(H2O)4/Na+III+H+], 3[(H2O)2/Na+II] and 6.6[(H2O)2/Na+I]; NaA(NaBO2) - 2[(H2O)4/Na+III], 3[(H2O)4/Na+II] and 6.86[(H2O)/Na+I]. The complete hydration of the α- and β cages of NaA amounts thus to 21,8 and 6,2 respectively H2O/u.c. and α-cage of NaA(NaBO2) – 26,3 H2O/uc. The mean molar integral adsorption entropy of water is ~-30,5 J/mol K less than the entropy of the bulk liquid. This value nearly the same as entropy of crystalline water so the mobility of water in the zeolitic matrix is solidlike.